Heat Shock Protein 90 (Hsp90) Selectively Regulates the Stability of KDM4B/JMJD2B Histone Demethylase - Ipenberg, Inbal (American Society for Biochemistry and Molecular Biology, 2013)
The family of KDM4A-D histone demethylases selectively demethylates H3K9 and H3K36 and is implicated in key cellular processes including DNA damage response, transcription, cell cycle regulation, cellular differentiation, senescence, and carcinogenesis. Various human cancers exhibit elevated protein levels of KDM4A-D members, and their depletion impairs tumor formation, suggesting that their enhanced activity promotes carcinogenesis. However, the mechanisms regulating the KDM4 protein stability remain largely unknown. Here, we show that the molecular chaperon Hsp90 interacts with and stabilizes KDM4B protein. Pharmacological inhibition of Hsp90 with geldanamycin resulted in ubiquitin-dependent proteasomal degradation of KDM4B, but not of KDM4C, suggesting that the turnover of these demethylases is regulated by distinct mechanisms. This degradation was accompanied by increased methylation of H3K9. We further show that KDM4B is ubiquitinated on lysines 337 and 562; simultaneous substitution of these residues to arginine suppressed the geldanamycin-induced degradation of KDM4B, suggesting that the ubiquitination of Lys-337 and Lys-562 targets KDM4B for proteasomal degradation upon Hsp90 inhibition. These findings constitute a novel pathway by which Hsp90 activity alters the histone code via regulation of KDM4B stability. This pathway may prove a druggable target for the treatment of tumors driven by enhanced KDM4B activity.